Dinâmica de proteínas: efeitos da hidratação em estrato córneo e de detergentes em albumina - Silva, Junaine Vasques da (2002)
The main function of the most superficial layer of the epidermis, the Stratum Corneum (SC), is to provide a physical barrier that controls the transepidermal water loss as well as the permeation of another substances in both directions across the skin. The SC is formed by anabolically dead cells, the terminally differentiated corneocyte, and its function is essentially accomplished by forming a highly insoluble protein structure on the surface of the corneocytes, termed the cornified cell envelope, and by impeding water diffusion across the SC by mortaring the corneocytes together by layers of skin-specific lipids, essentially ceramide, cholesterol and fatty acid. In this work the cell envelope of the SC was spin labeled with a sulfhydryl-specific nitroxide reagent to investigate the water content effects upon the protein dynamics directly in the intact tissue. A two-state model for the nitroxide side chain described the coexistence of two spectral components in the electron paramagnetic resonance (EPR) spectra. The so-called strongly immobilized component, S, is associated with the EPR signal of a motionally restricted nitroxide fraction having its N-O group hydrogen bonded to protein (rigid structure) while the weakly immobilized component, W, corresponds to the signal provided by the spin labels with higher mobility (~10 times greater) exposed to the aqueous environment. The relative populations between these two mobility states, S and W, are in thermodynamic equilibrium. The standard Gibbs free energy, enthalpy and entropy changes for transferring the nitroxide side chain from the state contacting the solvent, W, to the one contacting protein, S, indicated that the reduction of the SC water content to below ~h 0.69, g H2O per g dry SC, stabilizes the protein interacting state, S. Upon decreasing the SC hydration level below ~h 0.69 the segmental motion of the polypeptide chains and the rotational motion of the spin-labeled side chain were also constrained. To test our methodology in a pure and very well known protein, we also studied the effects of two types of detergents on the bovine serum albumin (BSA). Both detergents, the anionic sodium dodecyl sulfate (SDS) and the zwitterionic N-hexadecyl-N,N-dimethyl-3-ammonium-1-propanesulfonate (HPS) increase the mobility of the protein backbone and of the nitroxide side chain. The thermodynamic parameters indicated that these detergents destabilize the protein favoring less compact conformations. This work can also be useful to improve the spectral analysis of site-directed spin labeling, especially for a more quantitative description in terms of thermodynamic parameters.